International Vocational Education and Training Research: An Introduction to the Special Issue - Michael Gessler; Sandra Bohlinger; Olga Zlatkin-Troitschanskaia (European Research Network Vocational Education and Training (VETNET), 2021)
The seven articles in this special issue represent a wide range of international comparative and review studies by international research teams from China, Germany, India, Russia, Switzerland and Mexico. The presented projects are part of the national program "Research on the Internationalisation of Vocational Education and Training", funded by the German Federal Ministry of Education and Research (BMBF).   An adapted version of Urie Bronfenbrenner's ecological systems theory forms the conceptual framework of the special issue. The four system levels (micro, meso, exo and macro) are addressed by one article each. The article on the microsystem level focuses on the intended and implemented curricula in a cross-country comparison of China and Russia. The article on the mesosystem level aims at the development of a quality management model for vocational education and training (VET) institutions in India. At the exolevel, the regional structures of the education and employment systems in Mexico, particularly the cooperation between schools and companies in the hotel industry, are investigated. At the macrosystem level, the social representation of non-academic labour in Mexico is examined in terms of cultural artefacts. Furthermore, three overarching review studies systematise relevant research developments and approaches. The topics of the three review studies are European VET policy, transfer of VET and VET research. The scope ranges from the development of a comparative research tool to a summary analysis of over 5,000 individual publications.  Given the broad scope and heterogeneity of the findings, a summative conclusion would hardly be appropriate. Nevertheless, with regard to the model of the 'triadic conception of purposes in comparative VET research' that represents a heuristic for describing the purposes of international VET research, we conclude with an emphasis on a need of more criticality. In this context, one finding can be pointed out as an example: One review study found that most studies (here, with reference to VET transfer) refer to the recipient country without a comparative perspective. Thus, there is a clear demand for more comparative research following a critical-reflective approach.